TINGKAT PENDIDIKAN KELUARGA TERHADAP GOLDEN HOUR PASIEN STROKE DI RSUD ULIN BANJARMASIN - Rahmina, Yuniar; Wahid, Abdurahman; Agustina, Rismia (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2017)
The average time of arrival of the patient is exceeded golden hour (8.9 hours).The level ofeducation is one factor that leads to delays in stroke patients arrive at the hospital. The aim ofthis study to determine correlation between education towards golden hour stroke patients inhospitals Ulin Banjarmasin. This study used cross sectional descriptive analytic with accidentalsampling technique in 30 families of stroke patients in hospitals Ulin Banjarmasin. The study wasconducted from November to Desember, 2016 with the interview. Analyze result obtained thevalue of significance (2-tailed amounted to 0.773> 0.05 means that H0 is accepted, so there is nosignificant relationship between the level of education with the golden hour (p = 0.773). Thisindicates that the level of education is not related to the golden hour of stroke patients inhospitals Ulin Banjarmasin.